Mapping 123 million neonatal, infant and child deaths between 2000 and 2017 - Burstein, Roy; .......; Hay, Simon I (Nature, 2022)
This article was published in The Nature [ © 2019. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1038/s41586-019-1545-0 The Journal's website is at: https://www.nature.com/articles/s41586-019-1545-0#citeas